Merging Identities: Experiments in Dutch Primary Education - Renkema, Erik (Religious education, 2016)
In this article the authors present the results of their research of cooperation schools in the Netherlands. These schools are an exception in the dual educational system because they originate from a merger of a religiously neutral public school and a religious school. The data, provided by school principals, show key values of the cooperation schools. These values are compared to characteristics of public education. The authors also focus on the organization of religious education. This study is a first step in a broader research of Dutch experiments concerning the merging of different religious school identities.